2022
DOI: 10.1101/2022.02.05.479241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling the molecular mechanisms underlying the retrieval and extinction of morphine withdrawal-associated memories in the basolateral amygdala and dentate gyrus

Abstract: Despite their indisputable efficacy for pain management, opiates prescription remains highly controversial due to their elevated addictive potential. Relapse in drug use is one of the principal problems for addiction treatment, being drug-associated memories among its main triggers. Consequently, the extinction of these memories has been proposed as a useful therapeutic tool. Hence, by using the conditioned place aversion (CPA) paradigm in rats we investigated some of the molecular mechanisms that occurred dur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Classically, the activity of ERK1/2 and Akt/mTOR pathways, for their role in synaptoplasticity, had been considered vital for hippocampal declarative memory retrieval [32]. Nonetheless, ours and others' studies recently reported diminished mTOR and/or Akt phosphorylation after the recall of drug-associated aversive and rewarding memories in the NAcc, hippocampus and BLA [7,8,33,34]. The present investigation uncovers a different pattern of activation of these kinases in the BLA and DG determined by the kind of stressor that triggered the recall of cocaine-associated memories.…”
Section: Discussionmentioning
confidence: 64%
“…Classically, the activity of ERK1/2 and Akt/mTOR pathways, for their role in synaptoplasticity, had been considered vital for hippocampal declarative memory retrieval [32]. Nonetheless, ours and others' studies recently reported diminished mTOR and/or Akt phosphorylation after the recall of drug-associated aversive and rewarding memories in the NAcc, hippocampus and BLA [7,8,33,34]. The present investigation uncovers a different pattern of activation of these kinases in the BLA and DG determined by the kind of stressor that triggered the recall of cocaine-associated memories.…”
Section: Discussionmentioning
confidence: 64%
“…Also, the persistence of the CPA behavioral response may also depend upon the extinction procedure [26]. Indeed, extinction through reconditioning may occur more rapidly in a classical two-compartments CPA paradigm [31,32,36].…”
Section: Extinction and Spontaneous Recoverymentioning
confidence: 99%